PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BAGIAN PENGEMASAN (PENGANTONGAN) SEMEN DI PT. SWABINA GATRA GRESIK - Ayu Evida Restianah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study aims to examine the influence of work environment, workload and work discipline on employee performance. The number of samples is 95 employees of cement packing PT. Swabina Gatra Gresik. Data analysis used is multiple linear regression analysis.The results of this study concluded that the simultaneous test results of work environment, as well as work discipline have a significant effect on performance. The result of partial testing of work environment has significant effect on performance, work load has a significant effect on performance, work discipline has an effect on to performance.